Archive and Library Technique in Ancient Mesopotamia - Weitemeyer, Mogens (1956)
The Cuneiform Tablets — The Archives — Archive Technique in the Period of the III Dynasty of Ur — The Later Development of the Archives — The Origin and Development of the Libraries — Library Technique — Wax-covered Writing-boards — Conclusion.